Femtosecond laser application in keratoplasty – current view - Wylęgała, Edward; Milka, Michał; Tarnawska, Dorota; Dobrowolski, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Main purpose of this article is to present an actual review of application femtosecound laser in keratoplasty. Femtosecound laser keratome is a new option in corneal surgery that provides depth and diameter accuracy even at increased depth settings. It seems to be an ideal instrument to carry out stromal tissue cuttings in penetrating and lamellar keratoplasty as well as in refractive surgery. In this paper we also paid attention on adventages and disadventages of use FL, as well we compare this new technology with mechanical handheld microkeratomes.